THE LEGAL ASPECT OF CREDIT WITHOUT COLLATERAL IN INDONESIA (ASPEK HUKUM KREDIT TANPA AGUNAN DI INDONESIA) - Novenanty, Wurianalya Maria (Veritas et Justitia, 2018)
Using a legal normative approach,it can be stated that Act no. 10 of 1998 (amending Act No. 7 of 1992 re. Banking), in the event Bank considers loans or other financial schemes application, they are under the obligation, in accordance with Art. 8 of Act  no. 10 of 1998, conduct a thorough analysis of the debtor’s good faith, financial ability and willingness, and on that basis determine the risk of non-payment. In short, implement due care principles. The elucidation of Art. 8 elaborated on the bank’s duties: to decide wisely with due care in order to minimize the risk of default, that is by evaluating debtor’s character, capital in his/her possession, collateral offered, and economical/financial condition.  In legal practice, however, it is possible for Banks to offer loans without collateral. In such case, only two articles of the Indonesian Civil Code (arts. 1131 and 1132) would be applicable to offer protection against possible default. This paper discusses the above legal discrepancy in light of the role and function of collateral as protection against non-payment.